Analysis of Physical and Chemical Properties of Void Water Post Coal Mining Relationship With Aquaculture - Andi Nikhlani Nikhlani (Fakultas MIPA UNM, 2023)
Identification of the quality of void water after coal mining needs to be carried out in order to utilize the void as a place to raise fish. Identification of water quality, in the form of physical and chemical water. Physical and chemical parameters can influence the survival of cultivated biota, so research needs to be carried out to identify both physical and chemical water parameters related to aquaculture. The research method is taking and measuring water samples in situ and ex situ. Measurements were carried out at three (3) sampling points, sampling four times. The parameters observed are temperature, TSS, pH brightness, O2, BOD, COD, NO3, NO2, NH3, H2S. Descriptive analysis of water quality and comparing the quality standards of Provincial Regulations. East Kalimantan Number 2 of 2011, concerning Water Quality Management and Water Pollution Control. APPENDIX V, Class III The results of the water quality analysis physically show that the temperature is 29.5 –31oC brightness 135 – 285 Cm, TSS 13.75 – 27.5 mg/L, Chemical pH 7.42 – 7.68, O2 4.26 – 4.84 mg/L, BOD 0.64 – 1.84 mg/ L, COD 2.96 – 5.93 mg/L, NO3 0.026 – 0.049 mg/L, NO2 0.002 – 0.006 mg/L, NH3 0.01 – 0.13 mg/L and H2S 0 – 0.0087 mg/ L. Water quality parameters, both physical and chemical, still comply with the quality standards of East Kalimantan Province Regional Regulation Number 2 of 2011 concerning Water Quality Management and Water Pollution Control. The condition of post-coal mining void water, both physically and chemically, is still suitable for aquaculture.